COMMUNICATIVE ECHO QUESTIONS IN UKRAINIAN DISCOURSE - Artemenko, A. (Linguistic and Conceptual Worldviews, 2020)
This article researches communicative echo-questions in Ukrainian discourse. A communicative echo-question is a unique linguistic phenomenon which is used in the dialogue speech and has different pragmatic meanings and gives the speech communicative features. Communicative echo-questions are classified according to the pragmatic, structural and semantic aspects. They need the future research in Ukrainian discourse. Communicative echo-questions are a specific type of interrogative sentences, which repeat the previous phrase in the interrogative form and can follow different intentions. The research shows that communicative echo-questions can express indirect meanings of the communication and help resolve a conflict situation between speakers. In the research communicative echo-questions are identified on the basis of communicative relations between speakers. They can be used in different communicative situations of microdialogues. Communicative echoquestions can express politeness, rudeness, surprise and etc. The are divided into the following types, such as mental echo-questions, echo-questions which express surprise and echo-questions which are used for communicative pause. Echo-questions can be used by different groups of people, i.e. by men and women, old and young people, polite and rude persons etc. Echo-questions can be used in their speech to show their different inner state. It helps them to communicate positively avoiding conflict situations. Echo-questions are very interesting phenomenon which helps speakers to be polite with each other and communicate deeply. Social characteristics of echo-questions are also very important because they show different social features of situations and speakers with various status roles. Echo-questions help speakers to understand each other better and makes Ukrainian discourse more diplomatic. Pragmatic characteristics of communicative echo-questions show their functional role in Ukrainian discourse.